2005
DOI: 10.1021/jf048620x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Far-Infrared Irradiation on the Antioxidant Activity of Defatted Sesame Meal Extracts

Abstract: To determine the effect of far-infrared (FIR) irradiation on the antioxidant activities of sesame meal, half of sesame seeds were FIR-irradiated and then oil was extracted from the seeds. The resulting defatted sesame meal (DSM) was extracted with methanol, and the antioxidant activities of methanolic extract were determined. FIR irradiation of sesame seeds for 30 min increased the total phenol content from 34.0 to 59.0 muM and radical scavenging activity of DSM extracts from 26.40 to 68.76%. The induction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Lee et al first put forward that far IR radiation of rice can release more phenolic compounds in rice hull and thus increased the antioxidant activity of rice hull extract, defatted sesame meal extracts and water extracts from peanut hulls. It was also suggested that far IR radiation of green tea leaves at some temperatures could increase catechin contents and nitrite scavenging activity of green tea, with negligible effects on color [11][12][13][14]. Recently, Chen and colleagues successfully employed IR radiation to enhance the efficiency of tryptic proteolysis for peptide mapping [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al first put forward that far IR radiation of rice can release more phenolic compounds in rice hull and thus increased the antioxidant activity of rice hull extract, defatted sesame meal extracts and water extracts from peanut hulls. It was also suggested that far IR radiation of green tea leaves at some temperatures could increase catechin contents and nitrite scavenging activity of green tea, with negligible effects on color [11][12][13][14]. Recently, Chen and colleagues successfully employed IR radiation to enhance the efficiency of tryptic proteolysis for peptide mapping [15].…”
Section: Introductionmentioning
confidence: 99%
“…The DSME of roasted sesame seeds showed a much stronger antioxidant activity and reduced amounts of thiobarbituric acid-reactive substances values and volatile aldehydes than the DSME of unroasted sesame seeds in cooked turkey meats (10). Far-infrared irradiation of sesame seeds also markedly increased the antioxidant activity of DSME (11).…”
Section: Introductionmentioning
confidence: 91%
“…The two-phase decanter method preserved more of the phenolic content than the three-phase method by which the oil, water and husk is separated from the olive paste [84]. Far-infrared irradiation may be able to cleave covalent bonds and liberate phenolic acids from the repeating polymers present in sesame seeds [94]. Storage temperature was the major factor contributing to the changes in gallic acid content in mangos.…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 99%
“…The following list presents the food sources of phenolic acids and the papers in which they were discussed: Apples and apple juice [16, 39 -41], cherries [23, 42 -44], pears [45,46], must and wine [17, 20, 47 -54], sherry vinegar [55], sherry wine [56], winemaking waste solids [57], blueberries and blueberry juice [14, 58 -62], raspberries [4], strawberries [63,64], bayberries (Myrica rubra) [65], orange peel [66], mangos [67], passion fruit juice [68], dates [69], broccoli [70,71], lettuce [3], tomatoes [72 -74], potatoes [75,76], jicama [77], carrots [78], asparagus [79,80], leavy vegetables [81], legumes [22,53,82], olives and olive oil [83 -85], rye [86], oat [87], sorghum [88], wheat bran [89,90], cereal brans [91], barley [92], rice [93], sesame [94], sea buckthorn [95], mustard seeds [96], coffee beans [97], soybeans [98,…”
Section: Food Sourcesmentioning
confidence: 99%